Evaluating the Effectiveness of a Mathematics Word Problem Mobile App in Enhancing Problem-Solving Skills Among Lower Secondary Students in Kicukiro District, Rwanda - Thierry Niyitegeka; Dany Kamuhanda (Journal of Research in Mathematics, Science, and Technology Education, 2026)
Integrating technology into education has proven effective in enhancing both teaching and learning outcomes. In Rwanda, despite efforts to improve mathematics education, lower secondary students still perform poorly in solving word problems, as highlighted in national examination reports from 2019 to 2022 (NESA, 2023). This study aimed to evaluate the usability and effectiveness of a Mathematics Word Problem Mobile Application (Maths app) in improving students’ problem-solving skills. The Maths app was developed in alignment with Rwanda’s Competence-Based Curriculum (CBC), incorporating word problems across key mathematics topics such as Geometry, Algebra, Statistics, and Probability. The study used a mixed-methods approach and was conducted in two purposively selected day secondary schools in Kicukiro District. A total of 40 (32 males and 8 females) students participated in surveys, while a group of 20 (18 students and 2 teachers) took part in the usability evaluation. An additional 9 participants were interviewed. Purposive sampling targeted students with access to mobile phones and experienced mathematics teachers. Data collection methods included surveys, interviews, and the System Usability Scale (SUS). Quantitative data were analyzed using descriptive statistics and paired t-tests via SPSS, while qualitative responses were examined thematically. Findings revealed a significant improvement in students’ problem-solving skills, demonstrated by higher posttest scores. The Maths app received a high SUS score of 80.875, indicating strong usability. Participants highlighted the app’s alignment with the curriculum and its interactive features as major strengths. The study concludes that the Maths app is a valuable tool for enhancing mathematics learning among lower secondary students. It recommends future improvements, such as expanding the range of word problems and enabling offline access, to support broader implementation and accessibility in resource-constrained environments.